Contralesional Trunk Rotation Dissociates Real vs. Pseudo-Visual Field Defects due to Visual Neglect in Stroke Patients - Nyffeler, Thomas; Paladini, Rebecca E.; Hopfner, Simone; Job, Oliver; Nef, Tobias; Pflugshaupt, Tobias; Vanbellingen, Tim; Bohlhalter, Stephan; Müri, René M.; Kerkhoff, Georg; Cazzoli, Dario (Frontiers in Neurology, 2017)
In stroke patients, the clinical presentation of visual field defects (VFDs) is frequently accompanied by visual neglect, i.e., the inability to attend and respond to the contralesional space. However, the diagnostic discrimination between the lack of reactions to contralesional stimuli due to VFDs or due to visual neglect is challenging during clinical examination. This discrimination is particularly relevant, since both clinical pictures are associated with different therapeutic approaches and outcomes. The aim of the present study was to systematically investigate the effectiveness of trunk rotation towards the contralesional side – a manipulation dissociating the coordinate system of the trunk from that of the head and eyes – in disentangling real VFDs from ‘pseudo-VFDs’ that occur due to visual neglect. Twenty patients with a left-sided VFD after a right-hemispheric stroke (10 additionally showing visual neglect in neuropsychological testing, VFD+neglect; 10 without neglect, VFD) were tested with Goldmann perimetry in both standard and trunk rotation conditions. In the standard condition, both VFD and VFD+neglect patients showed a conspicuous narrowing of the left visual field. However, trunk rotation triggered strikingly different patterns of change in the two groups: it elicited a significant increase in visual field extension in the VFD+neglect group, but left visual field extension virtually unchanged in the VFD group. Our results highlight contralesional trunk rotation as a simple, viable manipulation in order to effectively and rapidly disentangle real VFDs from ‘pseudo-VFDs’ (i.e., due to visual neglect) during clinical examination.